Perancangan Sistem Penetas Telur Berbasis Intranet of Things - Supriyanto, supriyanto; Sugiharto, Sigit (LPPM Institut Pendidikan Nusantara Global, 2025)
Egg consumption is a cheap source of protein needed to meet the needs of the community. During certain seasons, during major holidays, the price of eggs increases due to a shortage of supply, which requires large quantities. Meanwhile, egg consumption and industry demand are very high, necessitating entrepreneurial motivation to produce laying hens. Research on the design of an intranet of things (IoT)-based egg incubator is aimed at Generation Z, encouraging them to become entrepreneurs by leveraging technology. The hope is that entrepreneurship through monitoring egg hatching with gadgets and automatic machine control can increase interest in egg hatching. The prototype egg incubator uses Arduino to monitor the required temperature, humidity, and periodic egg turning. Humidity is regulated by a Wemos D1 WiFi microcontroller using a DHT 22 sensor that can automatically detect humidity at 72% and a temperature of 37°C to 38°C. On the 10th day, the eggs are automatically turned. Egg hatching occurred unevenly for 21 days, from day 19 to 22 of incubation. The remaining eggs failed to hatch. Maintaining humidity by misting the eggs facilitates hatching or cracking the eggshells. The egg incubator design simulation using an Arduino Wemos D1 WiFi with an Intranet of Things network functioned well. The error rate for temperature was 1.78%. The error rate for humidity was 0.99%.